THE EFFECTIVENESS OF THE THINK PAIR SHARE MODEL BASED ON CULTURAL HERITAGE ON THE RESULTS OF IPS LEARNING - Mardiyah, Fatikhatul; Estiastuti, Arini (Universitas Negeri Semarang, 2019)
Based on the result of observation, interview, and data on learning outcomes conducted in 4th grade students at Elementary School of Cakra Cluster Semarang City, it was found that the social studies learning outcomes were not optimal because the learning model used by teacher was not appropriate . The purpose of this study was to test the effectiveness of Think Pair Share type of cooperative learning model based on cultural heritage on social studies learning outcomes of social, economic, cultural, ethnic, and religious diversity in the local provinces as the identity of Indonesia; and its relation to the characteristics of space. This was experimental research used a quasi experimental research design in the form of nonequivalent control group design. The data collection techniques used tests, observation, and documentation. The hypothesis test result showed that the t-test was 5.455, while the t-table value was 1.994. So that the tcount was greater than ttable (5.455> 1.994) which means that think pair share model based on cultural heritage was more effective on social studies learning outcomes. The experimental class n-gain test result was higher than the control class. The value of n-gain control class was of 0.3231 which was included in the low category and n-gain of the experimental class was 0.542 included in the medium category. The conclusion of this research was that think pair share model based on cultural heritage was effective to be used in social studies learning and could improve the learning outcomes of 4th grade students at Elementary School of Cakra Cluster Semarang City. So that the tcount was greater than ttable (5.455> 1.994) which means that think pair share model based on cultural heritage was more effective on social studies learning outcomes. The experimental class n-gain test result was higher than the control class. The value of n-gain control class was of 0.3231 which was included in the low category and n-gain of the experimental class was 0.542 included in the medium category. The conclusion of this research was that think pair share model based on cultural heritage was effective to be used in social studies learning and could improve the learning outcomes of 4th grade students at Elementary School of Cakra Cluster Semarang City. So that the tcount was greater than ttable (5.455> 1.994) which means that think pair share model based on cultural heritage was more effective on social studies learning outcomes. The experimental class n-gain test result was higher than the control class. The value of n-gain control class was of 0.3231 which was included in the low category and n-gain of the experimental class was 0.542 included in the medium category. The conclusion of this research was that think pair share model based on cultural heritage was effective to be used in social studies learning and could improve the learning outcomes of 4th grade students at Elementary School of Cakra Cluster Semarang City. 994) which means that think pair share model based on cultural heritage was more effective on social studies learning outcomes. The experimental class n-gain test result was higher than the control class. The value of n-gain control class was of 0.3231 which was included in the low category and n-gain of the experimental class was 0.542 included in the medium category. The conclusion of this research was that think pair share model based on cultural heritage was effective to be used in social studies learning and could improve the learning outcomes of 4th grade students at Elementary School of Cakra Cluster Semarang City. 994) which means that think pair share model based on cultural heritage was more effective on social studies learning outcomes. The experimental class ngain test result was higher than the control class. The value of n-gain control class was of 0.3231 which was included in the low category and n-gain of the experimental class was 0.542 included in the medium category. The conclusion of this research was that think pair share model based on cultural heritage was effective to be used in social studies learning and could improve the learning outcomes of 4th grade students at Elementary School of Cakra Cluster Semarang City. 542 included in the medium category. The conclusion of this research was that think pair share model based on cultural heritage was effective to be used in social studies learning and could improve the learning outcomes of 4th grade students at Elementary School of Cakra Cluster Semarang City. 542 included in the medium category. The conclusion of this research was that think pair share model based on cultural heritage was effective to be used in social studies learning and could improve the learning outcomes of 4th grade students at Elementary School of Cakra Cluster Semarang City.